Early autoantibody screening for type 1 diabetes: a Kuwaiti perspective on the advantages of multiplexing chemiluminescent assays - Al-Mulla, Fahd; Alhomaidah, Doha; Abu-Farha, Mohamed; Hasan, Amal; Al-Khairi, Irina; Nizam, Rasheeba; Alqabandi, Rawan; Alkandari, Hessa; Abubaker, Jehad (Frontiers in Immunology, 2023)
Type 1 diabetes (T1D) incidence has increased globally over the last decades, alongside other autoimmune diseases. Early screening of individuals at risk of developing T1D is vital to facilitate appropriate interventions and improve patient outcomes. This is particularly important to avoid life-threatening diabetic ketoacidosis and hospitalization associated with T1D diagnosis. Additionally, considering that new therapies have been developed for T1D, screening the population and individuals at high risk would be of great benefit. However, adopting such screening approaches may not be feasible due to limitations, such as cost, adaptation of such programs, and sample processing. In this perspective, we explore and highlight the use of multiplexing chemiluminescent assays for T1D screening and emphasize on their advantages in detecting multiple autoantibodies simultaneously, maximizing efficiency, and minimizing sample volume requirements. These assays could be extremely valuable for pediatric populations and largescale screening initiatives, providing a cost-efficient solution with increased diagnostic accuracy and deeper insights into T1D pathogenesis. Eventually, the adoption of such screening methods can help transform T1D diagnosis, especially in countries with high T1D prevalence, such as Kuwait, which will contribute to the development of novel therapeutic interventions, positively impacting the lives of those affected by T1D and other autoimmune diseases.